Synthesis and photopolymerization of new phosphorus containing dental monomers - Bilgici, Zeynep Saraylı. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Novel crosslinkers with phosphonate, phosphonic and carboxylic acid functions were prepared for use in dental materials. The crosslinkers were based on t-butyl - bromomethacrylate (TBBr) and synthesized by two different methods. The first method involved reaction of TBBr with Bisphenol A, followed by hydrolysis of t-butyl groups to acid chloride, and conversion to ester derivative using diethyl hydroxymethyl phosphonate. In the second method, TBBr was reacted with tetraethyl 5,5'-(propane-2,2-diyl)bis (2-hydroxy-5,1-phenylene) diphosphonate and tetraethyl 2,5-dihydroxy-1,4-pheylene diphosphonate to give two new monomers. The selective hydrolysis of the carboxylate and phosphonate groups of the monomers using trifluoroacetic acid and trimethylsilyl bromide (TMSBr) gave carboxylic acid and phosphonic acid containing monomers. A 1,6-heptadiene monomer with phosphonate functional groups was also synthesized from the reaction of TBBr and tetraethylmethylene diphosphonate. The photopolymerization behaviors of the synthesized monomers with 2,2-bis[4-(2- hydroxy-3-methacryloyloxy propyloxy) phenyl] propane (BisGMA), triethylene glycol dimethacrylate (TEGDMA) and glycerol dimethacrylate (GDMA) were investigated using Photo-Differential Scanning Calorimetry at 40 ºC using 2,2’-dimethoxy-2-phenyl acetophenone (DMPA) as photoinitiator.
Keywords: Monomers.; Polymers.; Photopolymerization.; Dental materials.